Letter - Hewlett, V. A. J.
013-0058-001 The National Union of Railwaymen HEAD OFFICE UNITY HOUSE, EUSTON ROAD, LONDON, N.W.1 LANCING BRANCH Secretary - V. A. J. HEWLETT, "St. Hilda", 20, North Farm Road, Lancing, Sussex. My ref:- your ref:- 25th November 1940. To The Secretary, T.U.C. Dear Sir, The above branch comprising 450 members resolve and demand that you use the whole weight of our movement to ensure the safety and retention in this country of Dr Negrin the Spanish Ambassador and in connection with this demand the resignation of Lord Halifax from the Foreign Office. Yours Faithfully, V.A.J.Hewlett, Branch Secretary. 292/946/13/58